2015
DOI: 10.1016/s0187-6236(15)72155-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and source identification of VOC species in Bogotá, Colombia

Abstract: RESUMENEn este trabajo se caracterizan compuestos orgánicos volátiles (VOC, por sus siglas en inglés) en aire ambiente en tres sitios de monitoreo ubicados en el perímetro urbano de Bogotá, Colombia. Se realizaron mediciones en línea de VOC con una resolución temporal de 30 min utilizando un cromatógrafo portátil Synstech Spectras. Las concentraciones medias de VOC fueron más altas en los dos sitios de muestreo, que se distinguen por sus actividades industriales y comerciales, así como por contar con una alta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Simpler urban/rural distinctions were not useful, e.g., the no-emission environments included urban, suburban, town, and city spaces, while the industrial environments included both rural and suburban communities. Based on median concentrations, outdoor alkane and TTVOC levels were highest at the industrial sites, followed by the near-road community and clear environments ( Figure 4 ), with patterns shown elsewhere at industrial and commercial sites [ 34 , 39 , 40 ]. Perhaps surprisingly, the lowest BTEX levels were found at the near-road schools, however, VOC emissions at highway speeds are now well controlled, e.g., Kimbrough et al [ 41 ] measured concentrations of BTEX and other VOCs near highways and major roads and found larger contributions from parking lots than the highway.…”
Section: Discussionmentioning
confidence: 99%
“…Simpler urban/rural distinctions were not useful, e.g., the no-emission environments included urban, suburban, town, and city spaces, while the industrial environments included both rural and suburban communities. Based on median concentrations, outdoor alkane and TTVOC levels were highest at the industrial sites, followed by the near-road community and clear environments ( Figure 4 ), with patterns shown elsewhere at industrial and commercial sites [ 34 , 39 , 40 ]. Perhaps surprisingly, the lowest BTEX levels were found at the near-road schools, however, VOC emissions at highway speeds are now well controlled, e.g., Kimbrough et al [ 41 ] measured concentrations of BTEX and other VOCs near highways and major roads and found larger contributions from parking lots than the highway.…”
Section: Discussionmentioning
confidence: 99%
“…PCA extracts the PCs from an i,j matrix, where i corresponds to the number of samples and j to the number of pollutants measured (correlated variables, in this case all the heavy metal species measured) (Franco et al, 2015). The PC extracted corresponds to pollutant (i.e., heavy metal) sources.…”
Section: Discussionmentioning
confidence: 99%
“…The first PC extracted includes the highest possible variability, and each succeeding compound accounts for as much as possible of the remaining variability (Han et al, 2006). The number of PCs that can be extracted depends on the retained variance of each PC (Franco et al, 2015). In this study, for the purpose of this exercise, a data matrix consisting of nine sites and six metals was considered (Rajaram et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors, in [34] have observed the aspect of O 3 where O 3 production consist of top five compounds come mainly from road traffic.…”
Section: J Fundam Appl Sci 2017 9(2s) 335-351mentioning
confidence: 99%